Distant And Near Interpuppilary Distance In 3448 Male And Female Subjects: Final Results (Annals of Medical Research, 2021)
Aim: To establish the normal standards for distant and near interpupillary distance (IPD) specific for age and sex in 3448 urban Turkish subjects from 7 to 40 years of age. IMethods: Turkish male (n=1852) and female (n=1596) subjects zere investigated for anatomical IPD. Subjects zere divided into three age groups; 7 to 15 year-old children (mean, 10.86±2.69), 16 to 25 year-old young adults (mean, 20.57±2.88), 26 to 40 year-old adults (mean, 30.87±4.55). The normative mean values at each age for 7 to 25 year-old group zere determined. The average values for IP measurements zith 3d, 10th, 25th, 50th, 75h, 90th and 97h percen tiles zere presen ted for 7 to 15 year-old group. The values zere compared zith standards derived from other ethnic populations.
Keywords: Interpupillary distance, anthropometry, hypertelorism, hypotelorism